Answer:
x=26
y=11
Step-by-step explanation:
y is equal to the one on the opposite side, so y=11
since 24 and the other side are equal, and the other side is x-2, you do 24+2=26
The solution of
are 1 + 2i and 1 – 2i
<u>Solution:</u>
Given, equation is ![x^{2}-2 x+5=0](https://tex.z-dn.net/?f=x%5E%7B2%7D-2%20x%2B5%3D0)
We have to find the roots of the given quadratic equation
Now, let us use the quadratic formula
--- (1)
<em><u>Let us determine the nature of roots:</u></em>
Here in
a = 1 ; b = -2 ; c = 5
![b^2 - 4ac = 2^2 - 4(1)(5) = 4 - 20 = -16](https://tex.z-dn.net/?f=b%5E2%20-%204ac%20%3D%202%5E2%20-%204%281%29%285%29%20%3D%204%20-%2020%20%3D%20-16)
Since
, the roots obtained will be complex conjugates.
Now plug in values in eqn 1, we get,
![x=\frac{-(-2) \pm \sqrt{(-2)^{2}-4 \times 1 \times 5}}{2 \times 1}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-%28-2%29%20%5Cpm%20%5Csqrt%7B%28-2%29%5E%7B2%7D-4%20%5Ctimes%201%20%5Ctimes%205%7D%7D%7B2%20%5Ctimes%201%7D)
On solving we get,
![x=\frac{2 \pm \sqrt{4-20}}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B2%20%5Cpm%20%5Csqrt%7B4-20%7D%7D%7B2%7D)
![x=\frac{2 \pm \sqrt{-16}}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B2%20%5Cpm%20%5Csqrt%7B-16%7D%7D%7B2%7D)
![x=\frac{2 \pm \sqrt{16} \times \sqrt{-1}}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B2%20%5Cpm%20%5Csqrt%7B16%7D%20%5Ctimes%20%5Csqrt%7B-1%7D%7D%7B2%7D)
we know that square root of -1 is "i" which is a complex number
![\begin{array}{l}{\mathrm{x}=\frac{2 \pm 4 i}{2}} \\\\ {\mathrm{x}=1 \pm 2 i}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bl%7D%7B%5Cmathrm%7Bx%7D%3D%5Cfrac%7B2%20%5Cpm%204%20i%7D%7B2%7D%7D%20%5C%5C%5C%5C%20%7B%5Cmathrm%7Bx%7D%3D1%20%5Cpm%202%20i%7D%5Cend%7Barray%7D)
Hence, the roots of the given quadratic equation are 1 + 2i and 1 – 2i
Answer:
![(x+2)^2 + (y-3)^2 = 10](https://tex.z-dn.net/?f=%28x%2B2%29%5E2%20%2B%20%28y-3%29%5E2%20%3D%2010)
Step-by-step explanation:
The standard equation for circle is
![(x-a)^2 + (y-b)^2 = r^2](https://tex.z-dn.net/?f=%28x-a%29%5E2%20%2B%20%28y-b%29%5E2%20%3D%20r%5E2)
where point (a,b) is coordinate of center of circle and r is the radius.
______________________________________________________
Given
center of circle =((-2,3)
let r be the radius of circle
Plugging in this value of center in standard equation for circle given above we have
![(x-a)^2 + (y-b)^2 = r^2 \ substitute (a,b) \ with (-2,3) \\=>(x-(-2))^2 + (y-3)^2 = r^2 \\=>(x+2)^2 + (y-3)^2 = r^2 (1)](https://tex.z-dn.net/?f=%28x-a%29%5E2%20%2B%20%28y-b%29%5E2%20%3D%20r%5E2%20%20%20%20%5C%20substitute%20%28a%2Cb%29%20%5C%20with%20%28-2%2C3%29%20%5C%5C%3D%3E%28x-%28-2%29%29%5E2%20%2B%20%28y-3%29%5E2%20%3D%20r%5E2%20%20%5C%5C%3D%3E%28x%2B2%29%5E2%20%2B%20%28y-3%29%5E2%20%3D%20r%5E2%20%20%20%20%281%29)
Given that point (1,2 ) passes through circle. Hence this point will satisfy the above equation of circle.
Plugging in the point (1,2 ) in equation 1 we have
![\\=>(x+2)^2 + (y-3)^2 = r^2 \\=> (1+2)^2 + (2-3)^2 = r^2\\=> 3^2 + (-1)^2 = r^2\\=> 9 + 1 = r^2\\=> 10 = r^2\\=> r^2 = 10\\](https://tex.z-dn.net/?f=%5C%5C%3D%3E%28x%2B2%29%5E2%20%2B%20%28y-3%29%5E2%20%3D%20r%5E2%20%20%20%20%5C%5C%3D%3E%20%281%2B2%29%5E2%20%2B%20%282-3%29%5E2%20%3D%20r%5E2%5C%5C%3D%3E%203%5E2%20%2B%20%28-1%29%5E2%20%3D%20r%5E2%5C%5C%3D%3E%209%20%2B%201%20%3D%20r%5E2%5C%5C%3D%3E%2010%20%3D%20r%5E2%5C%5C%3D%3E%20%20r%5E2%20%20%3D%2010%5C%5C)
now we have value of r^2 = 10, substituting this in equation 1 we have
Thus complete equation of circle is ![=>(x+2)^2 + (y-3)^2 = r^2\\=>(x+2)^2 + (y-3)^2 = 10](https://tex.z-dn.net/?f=%3D%3E%28x%2B2%29%5E2%20%2B%20%28y-3%29%5E2%20%3D%20r%5E2%5C%5C%3D%3E%28x%2B2%29%5E2%20%2B%20%28y-3%29%5E2%20%3D%2010)
Step-by-step explanation:
a−(6a−(5a−8))
a-(6a-5a+8)
a-6a+5a-8
6a-6a-8
0-8
=-8
so the answer doesn't depend on a
Answer:
The quotient of n and 6 is n/6, as quotient means divide.
for example, if it was "the quotient of 24 and 6", it would be 24/6, which is 4.